2014
DOI: 10.1007/s12104-014-9556-0
|View full text |Cite
|
Sign up to set email alerts
|

13C, 15N and 1H resonance assignments of receiver domain of ethylene receptor ETR1

Abstract: Ethylene plays versatile functions in regulating plant physiology. Although the high affinity ethylene receptor and its downstream regulators have been identified, the molecular recognition of the receptor interacting domains remains to be established. It has been speculated that the cytoplasmic signaling of the ethylene receptor is a two-component regulatory system involving the conserved receiver domain (RD). Here, we report the NMR chemical shift assignments for RD from Arabidopsis thaliana ethylene recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 11 publications
(12 reference statements)
0
6
0
Order By: Relevance
“…Fewer studies related to the properties of the ETR1-RD in solution have been performed. In addition to an X-ray diffraction study, the oligomerization status of the ETR1-RD in solution has been preliminarily investigated by NMR, and the results suggested that the RD was a monomer in solution [ 34 ]. Here, SDS-PAGE and FPLC analysis revealed that the ETR1-RD had a molecular weight of ~15 kDa in solution, further supporting the conclusion that it existed as a monomer in solution ( Fig 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fewer studies related to the properties of the ETR1-RD in solution have been performed. In addition to an X-ray diffraction study, the oligomerization status of the ETR1-RD in solution has been preliminarily investigated by NMR, and the results suggested that the RD was a monomer in solution [ 34 ]. Here, SDS-PAGE and FPLC analysis revealed that the ETR1-RD had a molecular weight of ~15 kDa in solution, further supporting the conclusion that it existed as a monomer in solution ( Fig 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…These properties indicate that the ETR1-RD is a highly folded domain with high conformational stability. The assignment was finished by adopting conventional backbone assignment strategy [ 34 ]. Based on this strategy, we were able to obtain the chemical shifts for all of the backbone nuclei.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The crystal structure of the ETR1 receiver domain has been determined, revealing a homodimer that is stabilized by the C terminus, which forms an extended b sheet (Müller-Dieckmann et al, 1999). However, in solution, dimerization may not occur (Hung et al, 2015), and a more recent structural model of the cytosolic domains of ETR1 indicates that the receiver domain of each monomer in a receptor may not come close enough to dimerize (Mayerhofer et al, 2015). Nonetheless, the modeling shows that the C-terminal tail could have a role in interactions with other proteins, including the receiver domains of adjacent receptor dimers (Mayerhofer et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it is noteworthy that phosphorylation-dependent dimerization of bacterial RDs has been shown to activate the DNA-binding domain of RRs (for a review, see Stock et al, 2000). However, ETR1 RD forms a homodimer in its unphosphorylated state (Muller-Dieckmann et al, 1999), and the recently published NMR spectra demonstrate that ETR1 RD is a monomer in solution (Hung et al, 2015). These data call into question the hypothesis stating the involvement of ETR1 RD s in phosphorylation-dependent formation of receptor clusters.…”
Section: Model Of the Cytosolic Portionmentioning
confidence: 99%